Analysis of Religiosity, Trust in Leader, and Team Cohesion on Green Organizational Citizenship Behavior Mediated by Green Employee Engagement - Arifin, Noor; Muafi, Muafi; Yulianto, Dwi Hery; Veisz, Adrienn (Jurnal Manajemen Bisnis, 2024)
Research aims: This study aims to analyze the impact of religiosity, trust in leaders, and team cohesion on green organizational citizenship behavior (Green OCB) through green employee engagement.Design/methodology/Approach: The study was conducted on 315 employees of Bank Syariah Indonesia using a multiple-stage cluster sampling technique with a purposive sampling method. Data was collected through a validated and reliable questionnaire, and analyzed using the Amos SEM application for hypothesis testing. Research finding: The research shows that religiosity significantly affects green employee engagement (P = 0.000). Trust in the leader, on the other hand, has an insignificant effect on green employee engagement (P = 0.426). Additionally, team cohesion has a significant effect on green employee engagement (P = 0.000). Furthermore, religiosity and team cohesion significantly affect Green OCB, with values of P = 0.002 and P = 0.028, respectively. Trust in the leader was found to have an insignificant effect on Green OCB (P = 0.680). It is important to note that trust in the leader did not significantly affect Green OCB after Z-testing. However, green employee engagement was found to mediate the relationship between religiosity and team cohesion on Green OCB, with values of (P = 0.003) and (P = 0.012), respectively. Theoretical Contribution/originality: This research contributes to the theory regarding the relationship between religiosity and trust in leaders within the context of green employee engagement. However, it indicates that trust in leaders does not appear to influence Green OCB. Instead, the study suggests that religiosity and team cohesion may play a significant role in increasing Green OCB. Additionally, the research underscores the mediating role of green employee engagement in the relationship between religiosity, trust in leaders, team cohesion, and Green OCB, particularly among employees in Islamic banking companies. Practitioners Contribution/implications: This research provides guidance for practitioners in Islamic banking to implement business models, with a particular emphasis on the importance of reliability for employees and leaders. This emphasis stems from its significant impact on the implementation of green management within the company. Research limitation/implications: The research data relies on perceptual measures, which may not fully capture the behavior of all respondents. Future research should consider factors such as the distribution of respondents, the frequency and timing of longitudinal studies, and other relevant variables that can be integrated into the model to provide a more comprehensive understanding.